2022
DOI: 10.3390/ph15101290
|View full text |Cite
|
Sign up to set email alerts
|

In Silico Studies on GCP-Lys-OMe as a Potential 14-3-3σ Homodimer Stabilizer

Abstract: 14-3-3 sigma is a vital negative cell cycle regulator. Its expression is consistently downregulated in many types of cancer through gene promoter hypermethylation or proteasomal degradation. 14-3-3 sigma needs to form a homodimer to be functional, while dimers are less prone to degradation than monomers. This suggests that a homodimer stabilizer may increase the tumor suppressive activities of 14-3-3 sigma. However, no known homodimer stabilizer of 14-3-3 sigma has been reported to date. Therefore, this study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(11 citation statements)
references
References 58 publications
1
9
1
Order By: Relevance
“…A multiparameter (size and count rate) analysis fitting algorithm was used for calculating the aggregation temperature, T agg . For DLS analysis on 14-3-3σ proteins at selected temperatures (25,42,50, and 60 °C), the volume distribution analysis of the protein across a range of different temperatures was conducted using a Litesizer100 (Anton Paar GmbH, Austria), with three measurements recorded at each temperature.…”
Section: ■ Materials and Methodsmentioning
confidence: 67%
See 4 more Smart Citations
“…A multiparameter (size and count rate) analysis fitting algorithm was used for calculating the aggregation temperature, T agg . For DLS analysis on 14-3-3σ proteins at selected temperatures (25,42,50, and 60 °C), the volume distribution analysis of the protein across a range of different temperatures was conducted using a Litesizer100 (Anton Paar GmbH, Austria), with three measurements recorded at each temperature.…”
Section: ■ Materials and Methodsmentioning
confidence: 67%
“…Our previous in silico work on GCP-Lys-OMe revealed that the basic functional groups of GCP-Lys-OMe, i.e., the guanidino and the primary amine groups, separated by approximately 12 Å, are critical for its interaction with the acidic residues at the dimer interface of 14-3-3σ, i.e., Glu20A, Glu20B, Glu91A, and Glu91B. 50 As the guanidino group is also observed in the side chain of Arg, while the primary amine group is observed at the N-terminus as well as the side chain of Lys, we hypothesized that a free N-terminus dipeptide with either one or both types of residues, with the two basic functional groups separated by a similar distance as observed in GCP-Lys-OMe, may also bind to the dimer interface of 14-3-3σ. Therefore, four different categories of dipeptides, i.e., Lys− Arg (KR), Arg−Lys (RK), Arg−Arg (RR), and Lys−Lys (KK), with different combinations of stereoisomers (LL, DL, DD, and LD) (to cater for the different distances between the two basic functional groups in the peptides) were generated (Table 1).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 3 more Smart Citations